Pengaruh Tax Knowledge, Tax Awareness Dan Trust In Government Terhadap Tax Compliance Kendaraan Bermotor (Studi Kasus Wajib Pajak Kendaraan Bermotor Di Desa Ampeldento Kecamatan Karangploso Kabupaten Malang) - Nuswantara, Setiaji Priyagung; Susyanti, Jeni; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The increasing cases of motor vehicle tax non-compliance have hampered the country's development and created various problems for economic growth. This is because the largest source of state income is in the tax sector paid by the public. Based on these problems, various strategic efforts are needed to release motor vehicle tax compliance, especially in Ampeldento Village, Karangploso District, Malang Regency. This research aims to see the influence that tax knowledge, Tax awareness and trust in the government have on Tax compliance in Ampeldento village. This research takes the type of explanatory research. The sampling technique used purposive sampling by determining the sample size using the Malhotra formula so that 100 taxpayers in Ampeldento Village were selected. Data processing uses SPSS 23 software. Based on the results of data processing that has been carried out, there is a significant influence between Tax knowledge on tax compliance, there is a significant influence of Tax awareness on tax compliance, there is a significant influence of tax trust in the government on tax compliance. Then tax knowledge, Tax awareness and trust in the government simultaneously influence tax compliance. Keywords: Tax knowledge, tax awareness, Trust In Government, tax compliance